2022
DOI: 10.1007/s11154-022-09717-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel treatments for congenital adrenal hyperplasia

Abstract: Patients with classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency (21OHD) need life-long medical treatment to replace the lacking glucocorticoids and potentially lacking mineralocorticoids and to lower elevated adrenal androgens. Long-term complications are common, including gonadal dysfunction, infertility, and cardiovascular and metabolic co-morbidity with reduced quality of life. These complications can be attributed to the exposure of supraphysiological dosages of glucocorticoids and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 96 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Adult patients usually require hydrocortisone at 15–25 mg/day fractioned in 2–3 doses. In Addison’s disease, dual-release hydrocortisone has demonstrated an improved metabolic profile and quality of life [ 21 ], especially when administered in fractionated daily doses [ 22 ]. Similar hydrocortisone modified-release formulations have been developed for CAH patients, showing an efficient suppression of the early morning ACTH peak and a more physiological circadian rhythm [ 23 ].…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Adult patients usually require hydrocortisone at 15–25 mg/day fractioned in 2–3 doses. In Addison’s disease, dual-release hydrocortisone has demonstrated an improved metabolic profile and quality of life [ 21 ], especially when administered in fractionated daily doses [ 22 ]. Similar hydrocortisone modified-release formulations have been developed for CAH patients, showing an efficient suppression of the early morning ACTH peak and a more physiological circadian rhythm [ 23 ].…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 99%
“…Other than hydrocortisone, prednisone, prednisolone, and methylprednisolone twice daily and dexamethasone once daily are being used. 21-OHD patients show adequate androgen suppression when treated with dexamethasone [ 21 , 25 ]. However, dexamethasone and, to a lesser extent, prednisone, are associated with worse long-term outcomes compared to hydrocortisone in classical 21-OHD [ 26 ].…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 99%
“…Individuals diagnosed with CAH require continuous medical intervention to compensate for deficient hormones and to regulate elevated androgen levels. Previous studies have shown that complications have persisted due to exposure to high doses of glucocorticoids and the continued high level of adrenal androgens [10]. Over the last few years, there has been substantial improvement in the development of new drugs and therapies for CAH.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, CAH remains a challenging condition in terms of best management, adequate hormonal substitution (to avoid both over and under treatment), and most practical surveillance protocol [41][42][43]. Adrenal tumours in these patients are generally associated with a late CAH diagnosis and a poor disease control [28].…”
Section: Introductionmentioning
confidence: 99%